(untitled)
bl ’kks/k i= esa ,d ’kgjh ok;q eaMy dks ,d lzksr fcUnq eku dj inkFkZ ds folj.k ds fy, ,d ekWMy laLFkkfir fd;k x;k gSA blds fiPNd dks ,d ifjHkkf"kr voLFkk ekuk x;k gS tgk¡ bldh lkanzrk ’kwU; gks tkrh gSA LFkkf;Ro Jsf.k;ksa dh miyC/k rduhdksa